Draft Genome Sequence of Saccharopolyspora rectivirgula - Pettersson, B. M. Fredrik (American Society for Microbiology, 2014)
We have sequenced the genome of Saccharopolyspora rectivirgula, the causative agent of farmer’s lung disease. The draft genome consists of 182 contigs totaling 3,977,051 bp, with a GC content of 68.9%.